Mechanisms of CAR T cell exhaustion and current counteraction strategies - Zhu, Xiaoying; Li, Qing; Zhu, Xiaojian (Frontiers in Cell and Developmental Biology, 2022)
The functional state of chimeric antigen receptor T (CAR T) cells determines their efficacy in vivo. Exhausted CAR T cells exhibit decreased proliferative capacity, impaired anti-tumor activity, and attenuated persistence. CAR T cell exhaustion has been recognized as a vital cause of nonresponse and relapse after CAR T cell therapy. However, the triggers and mechanisms leading to CAR T cell exhaustion remain blurry and complicated. Therefore, it is essential to clear the regulation network of CAR T cell exhaustion and explore potent solutions. Here, we review the diverse inducers of CAR T cell exhaustion in terms of manufacture process and immunosuppressive tumor microenvironment. In addition to the admitted immune checkpoint blockade, we also describe promising strategies that may reverse CAR T cell exhaustion including targeting the tumor microenvironment, epigenetics and transcriptomics.